2012
DOI: 10.1093/mnras/sts478
|View full text |Cite
|
Sign up to set email alerts
|

The faint source population at 15.7 GHz - I. The radio properties

Abstract: We have studied a sample of 296 faint (> 0.5 mJy) radio sources selected from an area of the Tenth Cambridge (10C) survey at 15.7 GHz in the Lockman Hole. By matching this catalogue to several lower frequency surveys (e.g. including a deep GMRT survey at 610 MHz, a WSRT survey at 1.4 GHz, NVSS, FIRST and WENSS) we have investigated the radio spectral properties of the sources in this sample; all but 30 of the 10C sources are matched to one or more of these surveys. We have found a significant increase in the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 30 publications
6
54
0
Order By: Relevance
“…This would also agree with recent findings (e.g. Whittam et al 2013Whittam et al , 2015. We note that almost half of these SMA observations are upper limits.…”
Section: The Sma Observationssupporting
confidence: 94%
“…This would also agree with recent findings (e.g. Whittam et al 2013Whittam et al , 2015. We note that almost half of these SMA observations are upper limits.…”
Section: The Sma Observationssupporting
confidence: 94%
“…Norris et al 2011). In general there is good agreement between the observed counts and that of semi-empirical simulations of Wilman et al 2008, but there maybe an excess in observed sources in the ∼0.5 -2 mJy flux density range, which may be related to flat-spectrum sources detected at sub-mJy levels at higher frequencies (>10 GHz, Whittam et al 2013;Franzen et al 2014). The 1.4 -5.5 GHz spectral index has also been determined for the 5.5 GHz sample.…”
Section: Discussionsupporting
confidence: 66%
“…There is now emerging evidence that the spectral index flattens again at sub-mJy levels, but the nature and properties of these faint radio sources is still unclear. The flattening of the average spectral index at sub-mJy levels has been observed in faint 5 GHz selected samples (Prandoni et al 2006;Huynh et al 2012b) and recently confirmed in sub-mJy samples selected at even higher frequencies (>10 GHz, Whittam et al 2013;Franzen et al 2014). However sub-mJy sources selected at 1.4 GHz or 610 MHz do not appear to exhibit a flattening in their average spectral index (Ibar et al 2009).…”
Section: Introductionmentioning
confidence: 67%
“…The 10C survey is complete to 1 mJy in ten different fields covering a total of ≈ 27 deg 2 ; deep areas covering ≈ 12 deg 2 , contained within these fields, are complete to 0.5 mJy, making the 10C survey the deepest high-frequency radio survey published to date. Whittam et al (2013) used data at a range of frequencies to study the spectral indices of 10C sources in the Lockman Hole. They found a significant change in spectral index with flux density; the median spectral index α (where S ∝ ν −α for a source with flux density S at frequency ν) calculated between 1.4 and 15.7 GHz changes from 0.75 for sources with S 15.7 GHz > 1.5 mJy to 0.08 for sources with S 15.7 GHz < 0.8 mJy.…”
Section: Introductionmentioning
confidence: 99%